Is There Any Difference Between Gonial Angle Values Measured on Digital Lateral Cephalograms and Orthopantomograms? - Kaya, Demet (Turk J Orthod, 2020)
OBJECTIVE: To determine whether there is a difference between the gonial angle (GoAng) values measured on digital lateral cephalograms (Lat Cephs) and orthopantomograms (OPGs) using a software. METHODS: This study was conducted by examining the digital Lat Cephs and OPGs of 51 patients (9 males, 42 females) who received orthodontic treatment. The mean age of the patients was 19.51±4.92 years. All digital radiographs were acquired with the same machine. The GoAng measurements were performed digitally using TotalCeph software. In order to evaluate the difference between the GoAngs measured on the digital Lat Cephs and OPGs, a paired t-test was used. To compare the two techniques (digital Lat Ceph and OPG) in terms of GoAng measurement, Bland-Altman analysis was used. The differences between the right and left GoAngs measured on the digital OPGs were evaluated using a paired t-test. The intraobserver reliability was assessed with the intraclass correlation coefficient (ICC) for repeated measurements. RESULTS: The intraobserver reliability was 0.99 for repeated measurements. There were no statistically significant differences between the GoAngs measured on digital Lat Cephs and OPGs (p=0.1). Bland-Altman analysis showed high levels of agreement between digital Lat Cephs and OPGs with a bias value of −0.4° for GoAng measurement. Moreover, the differences between the right and left GoAngs measured on the digital OPGs were not statistically significant (p=0.73). CONCLUSION: The results of this study demonstrated that the digital OPGs were as reliable as the digital Lat Cephs for measuring Go angles using a software.